2011
DOI: 10.1007/s00535-011-0477-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum gamma-glutamyltransferase level is associated with serum superoxide dismutase activity and metabolic syndrome in a Japanese population

Abstract: The serum gamma-glutamyltransferase level, even in the normal range, was significantly associated with anti-oxidative stress activity, the accumulation of oxidative stress, metabolic syndrome, and atherosclerosis. Measuring the serum gamma-glutamyltransferase level is simple and inexpensive, and this level can be used as a sensitive marker of oxidative stress and metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…For example, in men, fatty liver and an elevated serum GGT level were identified to be predictors of an increased mean carotid IMT and carotid plaque, whereas in women, neither of these two parameters were significantly associated with carotid atherosclerosis. These findings are in agreement with those of previous studies in which the association of an elevated serum GGT level with oxidative stress 12) and that of an elevated serum GGT level and fatty liver with CVD mortality 17) were found to be stronger in men than in women. Future studies are needed to clarify the reasons underlying these sex differences.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For example, in men, fatty liver and an elevated serum GGT level were identified to be predictors of an increased mean carotid IMT and carotid plaque, whereas in women, neither of these two parameters were significantly associated with carotid atherosclerosis. These findings are in agreement with those of previous studies in which the association of an elevated serum GGT level with oxidative stress 12) and that of an elevated serum GGT level and fatty liver with CVD mortality 17) were found to be stronger in men than in women. Future studies are needed to clarify the reasons underlying these sex differences.…”
Section: Discussionsupporting
confidence: 93%
“…The number of subjects with moderate to severe alcohol consumption was highest in the group with non-fatty liver and a serum GGT level of ≥ 83 IU/L, followed by the groups with fatty liver and a serum GGT level of ≥ 83 IU/L, non-fatty liver and a serum GGT level of 83 IU/L and fatty liver and a serum GGT level of 83 IU/L. The mean carotid IMT was higher in the subjects with fatty liver than in those without fatty liver, and the ratio of patients with carotid plaque was highest in the group with fatty liver and a serum GGT level of ≥ 83 IU/L, followed by the groups with non-fatty liver and a serum GGT level of ulation demonstrated a positive correlation between the serum GGT levels and increased carotid IMT values (although the analyses were univariate) 12) . Another large-scale study by Kozakova et al, in which the subjects were free of CVD, HT, DL, DM and metabolic syndrome, examined the association between the fatty liver index (FLI) (an index used to predict the presence of fatty liver) and carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, γGT is usually correlated with oxidative stress since it is involved in metabolizing extracellular glutathione which protects cells from oxidative stress by reacting with hydrogen peroxide. 20 To emphasize this results there is also the change in CK and CK-MB value; in fact, we found a decrease both of CK and CK-MB, but more in the latter (P<0.0173). This means that there was a rapid adaption in cardiac muscle but also in skeletal muscle since level decrease in a significant manner.…”
Section: Discussionmentioning
confidence: 64%
“…In this process, g-GTP generates ROS, including superoxide and hydrogen peroxide (16,17). It was reported that circulating g-GTP activity is positively associated with oxidative stress markers, such as nitrotyrosine and lipid peroxide (28)(29)(30). Furthermore, it was shown that C-reactive protein, an inflammatory marker, is positively associated with circulating g-GTP activity in healthy subjects and in patients with acute coronary syndrome (31,32).…”
Section: Discussionmentioning
confidence: 99%